2010
DOI: 10.1080/15715121003715107
|View full text |Cite
|
Sign up to set email alerts
|

3D simulation of flow around a single spur dike with free-surface flow

Abstract: In the present study, flow patterns around a single spur dike (also termed a groyne) with free-surface flow was simulated using a numerical model known as Fluent. The model solved the fully three-dimensional, Reynolds-averaged Navier-Stokes equation to predict flow near the structure where threedimensional flow is dominant. To treat the complex free-surface flow, the volume of fluid method with geometric reconstruction scheme was applied and turbulence was simulated using standard k − v equations. In this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…He observed that when the channel morphological changes were simulated with a series of floods, the initial rectangular channel became a compound channel and the flow pattern changed from a straight stream to a meandering stream. Yazdi et al (2010) simulated the flow pattern around single spur dike in a straight route using k-ε model in Fluent software. They studied the effect of discharge, and length and angle of the spur dike on shear stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…He observed that when the channel morphological changes were simulated with a series of floods, the initial rectangular channel became a compound channel and the flow pattern changed from a straight stream to a meandering stream. Yazdi et al (2010) simulated the flow pattern around single spur dike in a straight route using k-ε model in Fluent software. They studied the effect of discharge, and length and angle of the spur dike on shear stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Flow pattern in a channel bend is influenced widely by the secondary flow and centrifugal force. Yazdi et al (2010) by simulation of flow around a single spur dike found that varying the discharge has little effect on the reattachment length, but changing the length of the spur dike has considerable effects on the dimensions of the recirculation zone. Mousavi et al (2010) investigated the effects of relative curvature for a 908 bend with rigid bed using a T-shaped spur dike for three relative curvatures (2, 3 and 4).…”
Section: Introductionmentioning
confidence: 98%
“…This fraction was used to evaluate the lling level of the molten solder. It was also used to evaluate liquid phase in various CFD applications [13][14][15][16]. Wetting the PCB surface is important during wave soldering.…”
Section: Fluid Ow Modelingmentioning
confidence: 99%